DEVELOPMENT OF DERMATOGLYPHIC PRACTICUM GUIDE BASED ON GUIDED INQUIRY - Jodion Siburian; Gusti Ayu Muthia; Evita Anggereini (BIOEDUKASI, 2022)
This study aims to develop dermatoglyphic practicum guide based on guided inquiry and to determine students' creative thinking skills in using the practicum guide. This type of research is Research and development or R&D with the ADDIE development model. The subjects of this study were students of biology education at Jambi University who had contracted genetics courses and genetics practicum, namely students of the 2018 batch. The data analysis techniques in this study were quantitative and qualitative. The results of media validation and material validation showed an increase after revision with a media validation value of 71.60% (good) and material validation 89,05% (very good). The results of small group trials and large group trials of student perceptions of the practicum guide obtained a percentage of 84,82% % with (very good) and 89,24% for large group trials (very good). The use of practicum guides can improve students' creative thinking skills with the N-gain test score of 0.73 including the high category. Guided inquiry-based dermatoglyphic material practicum through the paired sample t-test, it is known that there is a significant effect of the use of practicum guides on students' creative thinking skills.